2019
DOI: 10.1007/s10120-018-00922-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for hyperprogressive disease during nivolumab as anti-PD1 treatment in patients with advanced gastric cancer

Abstract: Background Hyperprogressive disease (HPD) during treatment with anti-programmed death-1/programmed death-ligand 1 monoclonal antibodies has anecdotally been reported in some types of cancers, but is not well-characterized in patients with advanced gastric cancer (AGC). Methods Total 62 AGC patients treated with nivolumab in a single institution from September 2017 to April 2018 were enrolled in this study. Tumor responses were assessed according to Response Evaluation Criteria in Solid Tumors version 1.1, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
161
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(166 citation statements)
references
References 42 publications
3
161
1
1
Order By: Relevance
“…We performed enhanced computed tomography (CT) of the abdomen to determine the efficacy of three complete cycles of chemotherapy. The objective response rate of patients who underwent neoadjuvant chemotherapy and conversion therapy was evaluated according to the Response Evaluation Criteria in Solid Tumors (RECIST1.1) as follows: complete response (CR), partial response (PR), stable disease (SD) or progressive disease (PD) . Serum samples from 25 healthy volunteers, 20 patients with atrophic gastritis and 20 patients with gastric stromal tumours were provided during the course of the study.…”
Section: Methodsmentioning
confidence: 99%
“…We performed enhanced computed tomography (CT) of the abdomen to determine the efficacy of three complete cycles of chemotherapy. The objective response rate of patients who underwent neoadjuvant chemotherapy and conversion therapy was evaluated according to the Response Evaluation Criteria in Solid Tumors (RECIST1.1) as follows: complete response (CR), partial response (PR), stable disease (SD) or progressive disease (PD) . Serum samples from 25 healthy volunteers, 20 patients with atrophic gastritis and 20 patients with gastric stromal tumours were provided during the course of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Hyperprogressive disease refers to a remarkably accelerated tumor growth rate (TGR) that leads to poor prognosis in patients under ICB therapy particularly anti‐PD‐1/PD‐L1 agents . Currently, no consensus has been reached on the definition of HPD .…”
Section: The Role Of Medical Imaging In Immunotherapy: Response Assesmentioning
confidence: 99%
“…For instance, Champiat et al first reported HPD as a RECIST 1.1 progression before ICB therapy and a twofold or greater increase in TGR during immunotherapy, whereas Ferrar et al defined HPD as a disease progression at the first evaluation with at least an increase of 50% ΔTGR (the variation of TGR before and on treatment) (Figure ) . The incidence of HPD was reported to range from 7% to 29% across different types of carcinoma . However, the discordance in the definition of HPD across published literatures challenges the direct comparison of data.…”
Section: The Role Of Medical Imaging In Immunotherapy: Response Assesmentioning
confidence: 99%
See 2 more Smart Citations